Bending and bonding properties of sandwiched polymer concrete composites / Hamidah Mohd Saman ... [et al.] - Mohd Saman, Hamidah; Ibrahim, Azmi; Md. Taib, Yakub; Md. Ja’afar, Mohd. Faizal (Institute of Research, Development and Commercialisation (IRDC), 2006)
It is foreseen that the properties of Polymer Concrete (PC) can be further enhanced if the PC is bonded to or sandwiched between Glass Fibre Reinforced Plastic (GFRP) laminates, later termed as PC-GFRP system. In the present investigation, the performance of PC-GFRP was assessed in terms of its bending strength and bonding strength between PC and GFRP. Panels of PC size 500 mm × 500 mm × 20 mm were prepared. The panels then were cut into specimens of appropriate geometry and dimensions required for the tests. Four (4) different resin contents and different percentages of aggregate of different particle size distributions were employed in preparing the PC-GFRP specimens. A batch of PC specimens was layered with a Glass Fibre Reinforced Plastic (GFRP) laminate on one side (SSL) and the other batch PC specimens were sandwiched with two GFRP laminates (DSL). The PC-GFRP specimens were tested their bending strength under three-point load test and bonding strength between PC as a core material and glued GFRP laminate(s). The results showed that an increase in the resin content increases the bending strength of the PC regardless of the aggregate grading. The results also revealed that the PC specimens with well-graded aggregate recorded the highest bending strength, with coarser grading resulted in further increase. The bending strength of the PC-GFRP system improved significantly when the PC was externally reinforced with a GFRP laminate (SSL) but did not improve further when another layer of GFRP laminate was applied (DSL). The bonding strength between PC and GFRP was found to be increased as the resin content increases and the GFRP laminate bonded better to the PC as a core material if made of the overall aggregate size.